Risk of nephropathy can be detected before the onset of microalbuminuria during the early years after diagnosis of type 1 diabetes. - Schultz, C; Neil, H; Dalton, R; Dunger, D (2000)
OBJECTIVE: The early detection of a rise in albumin excretion within the normal range could permit early intervention to prevent the development of microalbuminuria (MA) in genetically susceptible subjects with type 1 diabetes. In the Oxford Regional Prospective Study we prospectively examined urine albumin excretion during the first years after diagnosis of childhood type 1 diabetes. RESEARCH DESIGN AND METHODS: Between 1986 and 1995, 511 subjects aged < 16 years were recruited at diagnosis and followed for a median of 6 years (range 1-14). In 78 subjects (designated cases), an annual assessment of the albumin-to-creatinine ratio (ACR) in three morning first-void urine samples detected MA (males: ACR > or =3.5 mg/mmol, females: ACR > or =4.0 mg/mmol in two of three urine samples). In 63 of these subjects and 396 normoalbuminuric diabetic control subjects, rates of change of the ACR were calculated as the slope of the ACR over diabetes duration. RESULTS: The baseline ACR (median [interquartile (IQ) range]), as measured at 1-2.5 years' duration of diabetes, was higher in microalbuminuric subjects than in the normoalbuminuric subjects (1.0 mg/mmol [0.6-2.1], n = 52, vs. 0.8 mg/mmol [0.6-1.2], n = 303; P = 0.02). The rate of increase of the ACR in the years before the onset of MA was higher in the microalbuminuric subjects than in the normoalbuminuric subjects (70% per year [37-149], n = 63, vs. 1% per year [-9 to 13], n = 396; P < 0.001). The mean HbA1c level after the onset of puberty was weakly correlated with the rate of change of the ACR (r = 0.11, P = 0.024, n = 418). CONCLUSIONS: Higher levels of ACR within the first 2 years after diagnosis and a significantly higher rate of increase of the ACR within the first 5 years from diagnosis can be detected in subjects who subsequently develop MA. HbA1c is a determinant of risk for MA, but pubertal factors have a greater effect on rates of progression of urine albumin excretion during adolescence in this cohort.